Forming of the most convenient bent constructional elements with a permissible strength given - Fligiel, Marek (Zielona Góra: Uniwersytet Zielonogórski)
In the present study, the limiting values are determined of the criteria quantities of optimal forming of the most convenient bent supporting structure for the case of static loads in the range of the Hooke?s law applicability. As the criterion of the most convenient constructional element, the following were accepted: the smallest length of the activity of internal forces as well as the equal potential and the gradient of the potential energy of elastic deformation at each point of the constructional element.
Keywords: the most optimal structure; supporting construction; the length of the activity of the internal forces